The Impact of Public Understanding of Usury on Debt and Receivable Behavior from an Islamic Perspective - Nurdin Mulyana; Ridla Mutiah; Agung Apriana (Lafadz Jaya Publisher, 2024)
Based on the framework of islamic teachings, economic activities carried out by humans to be developed have several rules and ethics or morality in Islamic law. Providing loans will help those in need as is the principle of loans or debts. The discussion about usury can be said to be classic both in the development of Islamic economic thought and in Islamic civilization because it is a complicated problem and often occurs in society. Based on research conducted at the Padamulya Village Taklim Country, Subang Regency, it shows that people who lack understanding about usury will tend to believe that usury is an addition that is too high, such as that made by loan sharks, while additions with small amounts are not usury. This research uses a qualitative research approach where qualitative research as a saientific method is often used and carried out by a group of researchers in the field of social sciences, including educational sciences. The result of the research show that people’s understanding about usury has an influence on debt and receivable behavior in the majelis taklim in padamulya village, subang district with a significantly low understanding value, thus showing a positive value, therefore there is a unidirectional relationship.